Interoperability for Enterprise Software and Applications : Proceedings of the Workshops and the Doctorial Symposium of the I-ESA International - International Conference on Interoperability of Enterprise Software and Applications 2010 : Coventry, England); Panetto, Herve; Boudjlids, Nacer (London : Wiley, 2013)
Within the framework of the Sixth I-ESA International Conference, supported by the INTEROP VLab (International Virtual Laboratory on Enterprise Interoperability, http://www.interop-vlab.eu), three workshops and a Doctoral Symposium have been organized in order to strengthen some key topics related to interoperability for enterprise applications and software. The workshops were selected to complement the conference topics, leaving more time to researchers for brainstorming and then coming up, at the end of the workshops, with new research directions for the future.
Towards a Model-Driven and Role-Configurable Methodology Suite for Enterprise and Service-Oriented InteroperabilityMediation Information System Engineering: Business and Logic Characterization in a Collaborative Situation; Role of Semantic Web in the Changing Context of Enterprise Collaboration; A Dynamic Knowledge Management Framework; Author Index.
Print version record.
John Wiley and Sons
Keywords: Internetworking (Telecommunication) -- Congresses; v; Internetworking (Telecommunication); Conference papers and proceedings